MODEL KUANTITATIF MANAJEMEN STRES KERJA DAN MOTIVASI UNTUK MENINGKATKAN KINERJA PETUGAS REKAM MEDIS DI RS ORTOPEDI PROF. DR. R. SOEHARSO SUR - Laili Rahmatul Ilmi (Universitas Jenderal Achmad Yani Yogyakarta, 2016)
Background: Workload may indirectly cause stress. The ability to manage work stress may affect staff’s motivation and performance. The staff performance will affect decision-making in improving the service quality. Objective: This study aimed to analyze the relationship between stress management, work motivation and work performance. Method: This was an analytic observational study with a cross sectional approach. A sample of 19 medical record staff, working at Prof. Dr. R Soeharso orthopedic hospital Surakarta, were selected for this study. A set of questionnaires were developed and administered to measure stress management, work motivation and work performance. Data were then analyzed with a bivariate correlation analysis. Results: There were statistically significant correlations between work stress management, work motivation and work performance. The ability to manage stress positively increased the motivation (r= 0,56; p= 0,013), as well as the work performance (r= 0,49; p= 0,036). Moreover, a higher motivation will lead to a higher performance (r= 0,42; p= 0,071). Conclusion: There were positive relationships between work stress management, work motivation and work performance. Key words: Work stress management, motivation, performance.